“An Empirical Study on the Impact of Social Media Marketing on Consumer Behaviour in the Cosmetic Industry, with Special Reference to Influencer Marketing” - Kalyani Mane, Amit Aggarwal (Journal of Informatics Education and Research, 2025)
The advent of social media platforms has transformed marketing especially in the cosmetic industry where visual content and consumer interaction are crucial. This paper empirically examines the influence of social media marketing with reference to influencer marketing, on consumer behaviour in the context of the Indian cosmetics industry. Basing on existing theories like Theory of Planned Behavior and Source Credibility Theory, the study investigates how influencers’ factors, like trustworthiness, expertise or reliability have an impact on consumer attitudes, purchase intentions, or brand loyalty. This study uses primary data collected from 384 respondents having social media active cosmetic consumers in urban India. The relationships among influencer marketing constructs and consumer behavior outcomes are investigated using quantitative methodologies based on regression and correlation analysis. Key results indicate that influencer credibility has a strong effect on consumer trust and purchase intentions, in particular when perceived content authenticity and engagement quality are high. Additionally the platform bias is highlighted, Instagram and YouTube emerge as the most influential channels in the beauty sector. The paper ends with managerial implications for brands, pointing out that a well-designed influencer strategy that leverages authenticity and audience relevance can drive brand resonance and consumer conversion in a crowded and competitive beauty market.